Changing photoluminescence spectra of graphene oxide by centrifugation treatments. Issue 11 (7th October 2013) - Kozawa, Daichi; Miyauchi, Yuhei; Mouri, Shinichiro; Matsuda, Kazunari; Yamaguchi, Hiroshi; Kumakura, Kazuhide
Abstract We conducted continuous‐wave photoluminescence (PL) measurements to study optical properties of graphene oxide (GO) before and after a centrifugation treatment. The pristine GOs show a PL peak around near‐infrared (NIR) region (∼1.7 eV). In contrast, the centrifuged GOs exhibit PL peaks at blue (∼2.8 eV) and UV (∼4.1 eV) region. The difference among the emission features in the pristine and centrifuged GOs originates from the change of major structure from the sp2 clusters to the quasi‐molecular structure. Our findings indicate tunability of PL from GOs in the range from NIR to UV region by the centrifugation treatment. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)